Amobilisasi Sel Lactobacillus Acidophilus FNCC116 Untuk Demineralisasi Limbah Kulit Udang Dalam Pengolahan Kitin - Betha, Ofa Suzanti; Setyahadi, Siswa; Suryadi, Herman (Majalah Ilmu Kefarmasian, 2009)
Chitin, a homopolimer, is the most abundant renewable natural resources after cellulose. Chitin and its derivatives hold many applications in agriculture, textile, pharmacy and medic. Chitin that extracted from waste shrimp shells by biological fermentation has better quality than chemical procees. Demineralization of chitin by biological procees use lactic acid as product of fermentation. Deproteinization of chitin use proteolytic activity of enzyme that produce by bacteria in fermentation. Lacto-bacillus acidophilus FNCC116 has been immobilized by entrapment methods and 2% sodium alginate in 0,2 M CaCl2 as the matric . The ability of immobilized Lacto-bacillus acidophilus FNCC116 cell in fermentation was tested. The fermentation that was carried out in medium which consist of 6% glukosa, 1,5% yeast extract, 0,003% MnSO4 0,003% FeSO4.7H2O, 0,02% MgSO4.7H2O and has been producted 2,24% lactic acid. Demineralization of waste shrimp shell with 30% immobilized Lactobacillus acidophilus FNCC116 cell has successfully decreased ash content tol 1,18% and produced lactic acid maximum 2.24%. Immobilization of Lactobacillus acidophilus FNCC116 cell promised an efficient method in bioproceesing of chitin recovery.